2015
DOI: 10.26694/2358.1735.2015.v2ed13579
|View full text |Cite
|
Sign up to set email alerts
|

A GOVERNANÇA CORPORATIVA COMO UM DIFERENCIAL PARA O VALOR DE MERCADO DAS EMPRESAS LISTADAS NA BM&FBOVESPA NO ANO DE 2012

Abstract: A governança corporativa, mecanismo que fomenta e reforça a transparência e a ética na gestão das organizações, vem sendo alvo de bastantes estudos, ultimamente. Isso vem se dando, principalmente, devido às descobertas recentes de grandes fraudes na gestão das corporações. Mecanismos de controle vêm tentando reduzir tais problemáticas, como, por exemplo, os níveis de governança corporativa diferenciados da BM&FBOVESPA. Esta pesquisa objetivou verificar se houve influência dos níveis diferenciados de govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Table 1 shows the divergence of results found by papers regarding the financial impacts of ESG investment. Mantovani and Belli (2019) and Silva and Câmara (2015) found significant relationships between ESG activities and the market value of companies. The latter stated that investors value organizations that have a high level of transparency, ethical values and that treat their stakeholders equally.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Table 1 shows the divergence of results found by papers regarding the financial impacts of ESG investment. Mantovani and Belli (2019) and Silva and Câmara (2015) found significant relationships between ESG activities and the market value of companies. The latter stated that investors value organizations that have a high level of transparency, ethical values and that treat their stakeholders equally.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…The expected signs are shown in Table 2. The expected sign for the ESG dummy variable is positive, since the works by Broadstock et al (2021), Jagannathan et al (2017), Kanamura (2021) and Silva and Câmara (2015) use stock market value data and find that ESG investments affect them positively. For the ROA*ESG interaction variable, the expected sign is positive, since the studies found in the literature present strong evidence that ESG practices and investments have a positive effect on companies' ROA (Azmi et al, 2021;Olli, 2021).…”
Section: Event Study and Financial Variables Of The Regression Modelsmentioning
confidence: 95%
See 1 more Smart Citation
“…Atesta-se, portanto, que, além de melhorar o relacionamento com seus investidores e influenciar o desempenho econônimo das empresas, as regras de gc causam impactos no vm delas, melhorando a qualidade do desempenho organizacional e garantindo a longevidade dos negócios (Lameira et al, 2007). Ademais, empresas que preservam um bom relacionamento com seus stakeholders e um comportamento ético adequado a estes, sendo conduzidas por princípios de governança, tendem a ser mais valorizadas pelo mercado acionista (Silva e Câmara, 2015). Em suma, a adoção de princípios de gc, como a transparência na utilização de indicadores que mostram o quanto de retorno a empresa gera em relação ao que é investido e aplicado pelo acionista na organização, além de proporcionar forte efeito sobre os ativos dela, torna-se relevante para o df e organizacional das empresas e, por consequência, para a valorização dessas no mercado de capitais (Melo et al, 2013)…”
Section: Introductionunclassified
“…Observa-se uma divergência de resultados quanto aos impactos financeiros do investimento ESG. Alguns autores encontraram evidências negativas ou mistas para a relação entre investimentos ESG e desempenho financeiro (Buallay, 2018;Crisóstomo et al, 2011;El Ghoul & Karoui, 2016;Jagannathan et al, 2017;Nguyen et al, 2020;Olli, 2021), enquanto outros estudos identificaram que empresas com maior investimento ESG possuem melhor desempenho financeiro (Azmi et al, 2021;Broadstock et al, 2021;Garcia et al, 2017;Kanamura, 2021;Mantovani & Belli, 2019;Silva & Câmara, 2015). Nesse sentido, não há consenso na literatura sobre o tema.…”
unclassified